Perceptions and Preparedness for Covid-19 Pandemic among Students of a Medical University - Rehmatullah, Khalida Naz Memon, Shazia Parveen, Maham Shah, Batool Bibi, Yousuf Ahmed Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The accomplishment of control of Covid-19 pandemic depends upon people’s readiness & preparedness of the medical professionals. The current study is expected to benefit the communities by assessing the knowledge of medical students regarding containment of this pandemic. Objectives: To assess the perceptions and readiness of the medical students regarding COVID-19. To determine association between various socio- demographic profile of study participants and their perceptions regarding Covid-19. Methodology: Three hundred & eighty four medical & dental students were selected by convenience sampling. Besides socio-demographic variables of medical students, students level of knowledge & perceptions regarding Covid-19 were recorded on a pre-designed & pre-validated questionnaire. Besides computing frequencies & percentages, the association among variables was performed by applying Chi-square test by taking p-value <0.05 as level of significance. Results: The response rate was 92.53%. The study participants had a high level of information (93.75%) regarding COVID19 outbreak. We did not find a single insignificant association between age of students & their perceptions regarding Covid-19 pandemic (p ≤ 0.01). Similar associations were observed between gender & level of education to the knowledge & perceptions regarding Covid-19 pandemic (p ≤ 0.01). Conclusions: The medical & dental students are very well aware about the Covid-19 pandemic & its control measures undertaken by government.